Reassortment of Avian Influenza A/H6N6 Viruses from Live Poultry Markets in Guangdong, China - Yuan, Runyu; Zou, Lirong; Kang, Yinfeng; Wu, Jie; Zeng, Xianqiao; Lu, Jing; Liang, Lijun; Song, Yingchao; Zhang, Xin; Ni, Hanzhong; Lin, Jinyan; Liao, Ming; et al. (Frontiers in Microbiology, 2016)
Since early 2013, H7N9-subtype avian influenza virus (AIV) has caused human infection in eastern China. To evaluate AIV contamination and the public risk of infection, we systematically implemented environmental sampling from live poultry markets in Guangdong Province. Through real-time polymerase chain reaction assays and next-generation sequencing, we generated full nucleotide sequences of all 10 H6N6 AIVs isolated during sampling. Focusing on sequence analyses of hemagglutinin genes of the 10 H6N6 AIVs revealed that the viruses were low pathogenic AIVs with the typical hemagglutinin cleavage site of P-Q-I-E-T-R-G. The hemagglutinin, neuraminidase, and nucleocapsid genes of nine AIVs were of ST2853-like (H6-subtype) lineage, ST192-like (N6-subtype) lineage, and HN573-like (H6-subtype) lineage, respectively; whereas the other five genes were of ST339-like (H6-subtype) lineage. However, the polymerase PB2 and nucleocapsid genes of one strain (HZ057) were of GS/GD-like (H5N1-subtype) and ST339-like lineages. Phylogenic analysis revealed that all eight genes of the 10 viruses belonged to Eurasian avian lineage. Altogether, the 10 AIVs were reassortants of different genetic groups of exchanges with the same virus subtype, thus illustrating the genetic diversity and complexity of H6N6-subtype AIVs in Guangdong Province.